Rethinking materialism: a question of judgements and enactments of power - Steinfield, L (2016)
This thesis traces the etymology of 'materialism' using a Foucauldian discourse analysis to bring to the fore the word’s use as discursive mode of power. Through examining over 5000 texts, spanning across 400 years, I trace a line from the origins of materialism in philosophical thought of the Renaissance and Enlightenment eras to its uptake in American rhetoric and integration into the consumer behaviour literature. This approach leads to a reconceptualization of materialism. Commonly viewed in consumer studies as a measurable value, trait, or motive inherent in the consumer, I situate materialism as external to the consumer. The word’s history, especially in consumer studies, demonstrates that it embodies moral condemnations. I find that accusations of materialism rise in discourses during moments of intense social dislocations. It is wielded by social groups as part of a play for status. In this analysis, concepts of power as per Foucault and social distinctions as per Bourdieu, are used to explain the motives residing behind the use of the word. These motives, which reflect sociocultural dynamics and geo-political agendas, manifest in the meanings attributed to 'materialism', and the directionality of the allegation. Thus I argue that 'materialism', at its essence, is an epithet used to advance or demobilise a set of interests. This is what I term, delegitimizing discourse—words used to debase other social groups. Studying 'materialism' as a case in point, I note that groups use delegitimizing discourse either an assimilative measure—rhetoric geared towards indoctrination—or as a defensive mechanism—rhetoric used to debase threatening elements and behaviours. It is hoped that this new perspective will encourage academics to be rethink their approach to studying materialism, or in the least, to be aware of what is being measured, and what moral judgements and interests they are perpetuating through their continued studies.